2019
DOI: 10.3390/su11195433
|View full text |Cite
|
Sign up to set email alerts
|

Responsible for Responsibility? A Study of Digital E-health Startups

Abstract: Responsible innovation (RI) has received increased attention from policymakers and academics as a solution to grand challenges and is viewed as the main driver for innovation. The United Nations has suggested 17 Sustainable Development Goals and responsible innovation can be seen as a tool that allows the movement of society towards reducing inequality, coping with environmental challenges and sustaining countries’ economic and societal development. Our knowledge of how businesses act responsibly in solving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 71 publications
(123 reference statements)
2
24
0
Order By: Relevance
“…However, as the dominant design emerges and a technological trajectory becomes established, so this room to maneuver becomes limited and the choice constrained. Extending the discussion of Stahl's maturity model [16], dimensions of RI, and the refined [74,75] framework, our exploratory cases suggest that there is value in maintaining a wider more inclusive approach and "delaying the freeze" in terms of innovation design can offer significant advantages in terms of quality of design and user acceptability.…”
Section: Theoretical Implicationsmentioning
confidence: 70%
“…However, as the dominant design emerges and a technological trajectory becomes established, so this room to maneuver becomes limited and the choice constrained. Extending the discussion of Stahl's maturity model [16], dimensions of RI, and the refined [74,75] framework, our exploratory cases suggest that there is value in maintaining a wider more inclusive approach and "delaying the freeze" in terms of innovation design can offer significant advantages in terms of quality of design and user acceptability.…”
Section: Theoretical Implicationsmentioning
confidence: 70%
“…This dichotomy triggers a question about the real substance of companies' claims and whether they are "walking-thetalk". The results suggest that RI may share the same path as CSR, which was originally meant to strategically shape the corporate identity of companies, but currently it is criticised for mainly focusing on corporate philanthropy [69,70]. There is a risk of "misusing" RI for marketing purposes by misleading consumers about social, ethical and environmental benefits of a product or service (e.g., greenwashing).…”
Section: Ri Conceptmentioning
confidence: 99%
“…Despite this variety of initiatives, the interviews show the absence of strategic CSR or CS tools explicitly devoted to innovation activities that would be integrated within a broader responsibility framework. Under RI, anticipation refers to systematic thinking about emerging critical issues and discovering new possibilities and opportunities [69]. Nevertheless, the results show that companies lack such systemic evaluation practices that would assess the degree to which a company's practices align with RI [7,23] or innovation activities that aim to reduce the uncertainty around potential negative impacts of innovation [11].…”
Section: Ri Evaluation and Controlmentioning
confidence: 99%
“…Information technology (IT) plays a major role in connecting all participants in the CH ecosystem and makes the delivery of the VP in the value network more efficient [79,83]. The literature review revealed how technology changes many aspects of business practice [16,[83][84][85]. The Internet has helped to convert many processes from lengthy (slow) to digital (fast), and many things are constantly digitized at every touchpoint.…”
Section: Rethinking Technologymentioning
confidence: 99%